การบริหารจัดการชุมชนเพื่อการเป็นเขตพัฒนาเศรษฐกิจพิเศษเชียงราย (COMMUNITY MANAGEMENT MODEL FOR CHIANG RAI SPECIAL ECONOMIC ZONE) - แก้วศรี ภูริพัฒน์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
The objectives of this study were to examine the state of community management in Chiang Rai Special Economic Zone, to investigate the problems of community management in Chiang Rai Special Economic Zone, and to develop a model to promote community management for Chiang Rai Special Economic Zone. The study was sectioned into 3 stages. Stage 1 was examining the state of community management in Chiang Rai Special Economic Zone. The samples were 45 participants (15 community leaders and 30 residents). That is, 5 community leaders and 10 residents were selected by purposive method from each of the three districts in Chiang Rai Special Economic Zone (Mae Sai district, Chiang Saen district, Chiang Khong district). The focus group discussion was used to collect the data in all 3 districts and content analysis was used to analyze the data. Stage 2 was investigating the problems in community management. The data collection used informal survey and interview. The samples were 454 community leaders and residents in Chiang Rai Special Economic Zone. The questionnaire and interview were used in data collection while content analysis and descriptive statistics were used in analyzing the data. Stage 3 was the development of a community management model. The samples were 20 participants including residents, community leaders, government officials, private sectors, and scholarly experts. The data collection used focus group discussion and content analysis was used in data analysis. The study found that the state of community management in Chiang Rai Special Economic Zone mainly focused on developing the physical infrastructure for business benefits and stimulating the community awareness and learning to be part of tourism management, trading, servicing, maintenance and transmission of local wisdom which is the unique characteristics of the local community. The overall problems in community management mainly involved physical infrastructure rather than other issues. That is, people did not have the chance to participate and share their ideas in the community management.Another problem also involved unclear budget planning and inappropriate budget distribution. The results on state and problems in community management were used to develop the community management model for Chiang Rai Special Economic Zone (CR-SEZ) entitled ECONOMICS Model consisting of 9 components. Also, the POLC management model was proposed for implementation and operation of the developed community management model for Chiang Rai Special Economic Zone as mandated by the government policy.